Economic effects of soil erosion in rainfed corn and the contribution of women on corn farming the case of Barangay Biao Escuela, Calinan District, Davao City and Barangay Tiburcia and Barangay Sampao, Municipality of Kapalong, Davao del Norte, Philippines - Alvarez, Yvonne Grace A. (School of Management, University of the Philippines Mindanao, 2016)
Corn in the Philippines is cultivated rain fed areas, and is often subjected to yield disruptions such as soil erosion. My study provided a better understanding on the situation of corn farmers in rain fed areas of Davao region and measured the impact of soil erosion on farm productivity, farm income, expenditure, children?s food and nutrition intake, and assessed the contribution of women in corn farming. Analysis revealed that soil erosion significantly affects the productivity of corn farming causing a 4.65% in yield reduction in slightly eroded areas relative to no erosion corn areas. This led to a decrease in farming income, causing farmers from slightly eroded areas to find alternative sources of livelihood. Expenditure analysis revealed that households in slightly eroded areas have higher expenditure even though they have lower income and are significantly spending for cereals and cereal preparation. Results of food intakes of children in both areas of erosion, showed that among all the food types identified, only yam, eggplant, mung bean, coconut milk, pork, meatloaf, and hotdog are significantly consumed in higher proportions by children from slightly eroded areas. Results from nutritional intake revealed that in terms of daily energy requirement, both areas were inadequate with children in slightly eroded areas having the lowest and were only significantly consuming higher intakes of vitamins A,D, and calcium. The performance of women as farmers when compared to male farmers showed that there were no difference between the gender of the farmer and the performance in farming. Thus, this research calls for immediate and appropriate farming extension programs on areas affected by erosion in order to enhance the productivity of farmers and in turn increase their farming income.